Pemeriksaan Kesehatan Gratis dan Edukasi Penyakit Tidak Menular Hipertensi - Joni Siagian; Khairunnisa Batubara; Amelia Dini Anggraini Silalahi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This Community Service (PkM) activity is intended to solve problems that exist in certain community groups in adulthood. Hypertension can result in dangerous diseases such as heart disease and stroke if not treated in the long term. The PkM team provides education to provide solutions. The PkM activity implementation team collaborates with the local village government. The method used in this activity is counseling on hypertension from a team of nursing lecturers and nursing students during Field Learning Practice starting from anthropometric examination activities, blood pressure, blood sugar supplemented by interviews with the community. The respondents used in this educational activity were 35 people. The output of the PkM that has been implemented is in the form of reports and publications of articles so that they can be accessed by all parties who need related articles.